Metamorphic ultrahigh-pressure tourmaline: structure, chemistry, and correlations to P-T conditions: - Ertl, Andreas; Marschall, Horst R.; Giester, Gerald; Henry, Darrell J.; Schertl, Hans-Peter; Ntaflos, Theodoros; Luvizotto, George Luiz; Nasdala, Lutz; Tillmanns, Ekkehart (American mineralogist, 2010)
Tourmaline grains extracted from rocks within three ultrahigh-pressure (UHP) metamorphic localities have been subjected to a structurally and chemically detailed analysis to test for any systematic behavior related to temperature and pressure. Dravite from Parigi, Dora Maira, Western Alps (peak P-T conditions ~3.7 GPa, 750 °C), has a structural formula of X (Na 0.90 Ca 0.05 K 0.01 ⃞ 0.04 ) Y (Mg 1.78 Al 0.99 Fe 2+ 0.12 Ti 4+ 0.03 ⃞ 0.08 ) Z (Al 5.10 Mg 0.90 )(BO 3 ) 3 T Si 6.00 O 18 V (OH) 3 W [(OH) 0.72 F 0.28 ]. Dravite from Lago di Cignana, Western Alps, Italy (~2.7-2.9 GPa, 600-630 °C), has a formula of X (Na 0.84 Ca 0.09 K 0.01 ⃞ 0.06 ) Y (Mg 1.64 Al 0.79 Fe 2+ 0.48 Mn 2+ 0.06 Ti 4+ 0.02 Ni 0.02 Zn 0.01 ) Z (Al 5.00 Mg 1.00 )(BO 3 ) 3 T (Si 5.98 Al 0.02 )O 18 V (OH) 3 W [(OH) 0.65 F 0.35 ]. “Oxy-schorl” from the Saxonian Erzgebirge, Germany (≥4.5 GPa, 1000 °C), most likely formed during exhumation at >2.9 GPa, 870 °C, has a formula of X(Na 0.86 Ca 0.02 K 0.02 ⃞ 0.10 ) Y (Al 1.63 Fe 2+ 1.23 Ti 4+ 0.11 Mg 0.03 Zn 0.01 ) Z (Al 5.05 Mg 0.95 )(BO 3 ) 3 T (Si 5.96 Al 0.04 )O 18 V (OH) 3 W [O 0.81 F 0.10 (OH) 0.09 ]. There is no structural evidence for significant substitution of [4] Si by [4] Al or [4] B in the UHP tourmaline (<T-O> distances ~1.620 Å), even in high-temperature tourmaline from the Erzgebirge. This is in contrast to high-T-low-P tourmaline, which typically has significant amounts of [4] Al. There is an excellent positive correlation (r 2 = 1.00) between total [6] Al (i.e., Y Al + Z Al) and the determined temperature conditions of tourmaline formation from the different localities. Additionally, there is a negative correlation (r 2 = 0.97) between F content and the temperature conditions of UHP tourmaline formation and between F and Y Al content (r 2 = 1.00) that is best explained by the exchange vector Y AlO(R 2+ F) -1 . This is consistent with the W site (occupied either by F, O, or OH), being part of the YO 6 -polyhedron. Hence, the observed Al-Mg disorder between the Y and Z sites is possibly indirectly dependent on the crystallization temperature.